A Seashore Vitality Assessment framework for blue economy growth evaluation in coastal cities: the case of Wuyuan Bay, Xiamen - Zhang, Yang; Huang, Faming; Xue, Xiongzhi; Lin, Yanhong; Zhang, Zhuohang; Xu, Mengjie; Song, Peng (Frontiers in Marine Science, 2025)
IntroductionThe "blue economy" is an invaluable part in the pursuit of Sustainable Development Goal 14 (SDG14), with China's active engagement holding significant implications for global marine governance. However, a quantitative, regionally scaled “bottom-up” assessment framework for blue economy growth and actionable implementation strategies remain underexplored.MethodsThis study addresses this gap by first utilizing a Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis to identify the marine development direction of Wuyuan Bay. Subsequently, a novel Seashore Vitality Assessment (SVA) framework, integrated with the Gray Relation Analysis (GRA) method, is constructed to inform Marine Spatial Planning (MSP) for sustainable development. Applied to the typical case of Wuyuan Bay, this framework effectively measures the blue economy growth level of coastal zones.ResultsThe SVA results unveil that economic vitality, particularly in sea areas, is the primary factor limiting blue economy growth, highlighting MSP as the most effective pathway for enhancement, tailored by distinct seashore types. The derived marine development direction for Wuyuan Bay is “ecology + tourism + sports”, leading to four comprehensive MSP strategies.DiscussionThis study contributes by filling a critical research gap in urban vitality assessment within marine and coastal zones, emphasizing the integrated land-sea interface and the spillover effects of marine influences. The framework's simplicity and effectiveness offer a valuable reference for other regions in formulating blue economy growth plans and fostering multi-stakeholder benefits. Future research should deepen data analysis through longitudinal datasets and advanced statistical modeling, systematically incorporate cultural vitality metrics using diverse data sources including statistical yearbooks and web search indices, and consider the effectiveness evaluation and adaptive regulatory schemes for MSP.